2017
DOI: 10.1002/jocb.221
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as Identity Skill? Late Adolescents' Management of Identity, Complexity and Risk‐Taking

Abstract: The link between identity and creativity has received surprisingly little attention from developmental psychology researchers, although flexibility and the ability to generate multiple solutions to problems are key competences for contemporary society based on continuous innovation and de‐standardization of development trajectories. These competences are critical for identity formation processes, mainly during late adolescence when young people have to explore and commit to defining themselves. This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…The four subscale scores were calculated by summing responses to items for each subscale ( Tong et al, 2015 ). In previous studies, the scale has shown good reliability and validity ( Jin et al, 2016 ; Sica et al, 2017 ; He et al, 2018 ). In the present study, the Cronbach’s alpha of each subscale in this study ranged from 0.638 to 0.794.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The four subscale scores were calculated by summing responses to items for each subscale ( Tong et al, 2015 ). In previous studies, the scale has shown good reliability and validity ( Jin et al, 2016 ; Sica et al, 2017 ; He et al, 2018 ). In the present study, the Cronbach’s alpha of each subscale in this study ranged from 0.638 to 0.794.…”
Section: Methodsmentioning
confidence: 91%
“…Trait creativity was measured using the Williams Creativity Aptitude Test (WCAT), which is part of the Creativity Assessment Packet ( Williams, 1980 ). We used the Chinese version developed by Lin and Wang (1997) , which consists of 50 items and four dimensions: curiosity (inclination to explore, or play with an idea), imagination (predisposition to visualize and construct mental images, or feel intuitively), challenge (the tendency to look for new alternatives and solutions to problems, to restore order out of chaos), and risk-taking (the inclination to act under unstructured conditions and to defend one’s own ideas) ( Gostoli et al, 2017 ; Sica et al, 2017 ). All items range from 1 (completely disagree) to 3 (completely agree), except for eight items with an inverse direction.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from this evidence, a line of research has focused on the possible contribution of creativity to self/identity definition. Thus, creativity was considered either as a component or a domain of identity (creative identity; Dollinger et al, 2004 ), or as a resource in terms of positive self-definition and support for identity achievement (Barbot, 2008 ; Barbot & Heuser, 2017 ; Barbot & Lubart, 2012 ; Sica et al, 2017 ).…”
Section: Personal Skills For Identity Development (Psid): the Emotional-divergent Aspect Of Creativity Agency Personal Growth Initiativementioning
confidence: 99%
“…People revise, and alter their identity based on the situation (Ibarra & Barbulescu, 2010). Identity, makes a critical contribution to employee creativity (Sica, Ragozini, Palma, & Sestito, 2017). Creativity can be interpreted as an individual ability to adjust (Csikszentmihalyi, 1996).…”
Section: Literature Review Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…Creativity can be interpreted as an individual ability to adjust (Csikszentmihalyi, 1996). Creativity was considered a personality trait useful for adaptation and maladjustment of individuals to environments (Sica, Ragozini, Palma, & Sestito, 2017). According to Csikszentmihalyi (1996), creative individuals are remarkable for their ability to adjust in any given situation and to make do with whatever is at hand to reach their goals.…”
Section: Literature Review Theoretical and Conceptual Backgroundmentioning
confidence: 99%